Assessment of Effective Learning Transfer at Workplace after a Formal Faculty Development Program: Evaluating Learning Transfer after Faculty Development - Amin, Sarah; Qaiser, Aasma; Siddique, Muhammad Omer; Qureshi, Waseem Pasha; Hussain, Warda; Ali, Waqas (Pakistan Journal of Health Sciences, 2024)
Higher education institutions use Faculty Development Programs (FDPs) as organized learning opportunities to improve the abilities, knowledge and skills of its faculty members. Objective: To evaluate the faculty development program using Kirkpatrick Model and acknowledging the program's importance in medical education. Methods: A non-probability purposive sample of 27 faculty members was used in the quantitative quasi-experimental design. Pre- and post-tests or intervention were conducted as part of the CBL facilitation skills training included in the faculty development program after three and six months, with a particular emphasis on CBL facilitation skills comprising four domains: teaching skills, teacher knowledge, student happiness, and environmental factors. Results: The analysis revealed that participants demonstrated significantly higher mean scores across all four domains in the second evaluation (post-test/ intervention) compared to the first evaluation (pre-test/ intervention). Each domain showed a p<0.05, indicating statistically significant improvements. These results suggest that the CBL facilitation skills training program was effective in enhancing participants' skills. Moreover, the evaluation reached level 3 of the Kirkpatrick model, signifying a positive transfer of learning to the workplace, with observed improvements in teaching skills and behavior change among participants. Conclusions: Faculty development programs were mandatory for learning transfer and improving teaching skills at workplace. Proper program evaluations were equally important to see whether learning transfer was actually happening at workplace or not